2009
DOI: 10.1007/s12062-010-9021-5
|View full text |Cite
|
Sign up to set email alerts
|

House Price Appreciation in Old Age: Analysis and Issues for the Use of Reverse Mortgages as a Retirement Funding Strategy in Australia

Abstract: This paper investigates whether the houses of Australian elderly home owners appreciate at below the market rate and examines the issues this may raise for the use of reverse mortgages as a retirement funding strategy in Australia. The viability of reverse mortgages where elderly home owners effectively borrow against their housing equity depends strongly on house prices appreciating enough to offset the outstanding loan balance at the end of the loan tenure. This paper's findings indicate that after controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In this context since 2012 in Australia, reverse mortgage borrowers have a "non-recourse" clause in the loan agreement stating that they will not owe the lender more than the sale value of the home. Interestingly, both Ong (2009) in Australia and Davidoff (2006) in the US show that homeowners aged over 75 spend considerably less on home maintenance thereby potentially depreciating the eventual sale value of their properties. Weber and Chang (2006) discuss many ethical considerations that family, friends, and lenders need to consider in assisting the borrower to make the right decision for their needs, including the autonomy, the dignity and overall welfare of the borrower.…”
Section: Literature: Reverse Mortgages Perspectives and Financial Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context since 2012 in Australia, reverse mortgage borrowers have a "non-recourse" clause in the loan agreement stating that they will not owe the lender more than the sale value of the home. Interestingly, both Ong (2009) in Australia and Davidoff (2006) in the US show that homeowners aged over 75 spend considerably less on home maintenance thereby potentially depreciating the eventual sale value of their properties. Weber and Chang (2006) discuss many ethical considerations that family, friends, and lenders need to consider in assisting the borrower to make the right decision for their needs, including the autonomy, the dignity and overall welfare of the borrower.…”
Section: Literature: Reverse Mortgages Perspectives and Financial Theoriesmentioning
confidence: 99%
“…As with all property/financial products there are costs, through potential fee structures depending upon the product provider, and risks. Indeed, earlier research by Ong (2008Ong ( , 2009 illustrated that complex issues surround participation in reverse mortgages and that there is the risk of being left with little equity to meet financial emergencies. Some of these risks have been clearly articulated in a report by the Australian Securities & Investment Commission ([ASIC] 2018) which, nevertheless, found that reverse mortgages have helped older Australians achieve their immediate financial objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Although they refer to “moral hazard”, a failure to maintain the property may be owing to incapacity attributable to old age or because of (fear of) lack of income. Based on an analysis of Australian data, Ong (2009) found that being 75 years of age or older lowers annual house price appreciation by 1.4 percentage points and further that being aged 75 or older lowers home improvement expenditure by over AUD 3,000 per year and is attributable to a decline in income in old age. Based on a review of American Housing Survey data for the period 1985–2001, Davidoff (2004) observed that annual spending by homeowners 75 and older is ∼270 USD less on routine home maintenance and 1,100 USD less on home improvement than by younger homeowners with similar homes.…”
Section: An Alternative Her Product and Its Pricingmentioning
confidence: 99%
“…The pricing and hedging of non-recourse loan risk has been extensively studied by Chen et al (2010), Li et al (2010), Lee et al (2012), Kogure et al (2014), Shao et al (2015), and Wang et al (2016), to name a few. Despite most retirees appearing to be unaware of or unfamiliar with RM, this loan type has been developed to become the most popular and widely-available equity release product in many countries, such as the US (Shan 2011), UK (Sharma et al 2022), Australia (Ong 2009), Korea (Kim and Li 2016), Japan (Mitchell and Piggott 2004), Spain (Debon et al 2013), etc. In addition to using RM as a source of financial income, Stucki (2006), Andrews and Oberoi (2015), and Bonnet et al (2019) also explored the opportunities and challenges in linking RM with long-term care (LTC) needs and financing.…”
Section: Introductionmentioning
confidence: 99%